Review: The Application of Coach Leadership Models to Coaching Practice: Current State and Future Directions - Vella, S.; Oades, L.; Crowe, T. (International Journal of Sports Science and Coaching, 2010)
The purpose of this concept/review article is to critically discuss the application of sports coaching leadership models to coaching practice. The focus of the discussion will be on the coherence and impact of the numerous models in the current literature, and the accumulated impact that they have on practitioners. This discussion will be framed in current conceptions of sports coaching and expected athlete outcomes. This article can serve an important role in the continuing dialogue about the essence of sports leadership; particularly in relation to how it is defined, how it is measured, and how the leadership literature can be applied in the field.